Crime prevention : principles, perspectives and practices - Sutton, Adam; Cherney, Adrian; White, R. D. (Robert Douglas), 1956- (Cambridge : Cambridge University Press, 2014)
This book examines a range of Australian examples within an international context. Part 1 presents an overview os the history and theory of crime prevention, featuring chapters on social prevention, enviornmental prevention and evaluation. Part 2 explores the practice of crime prevention and the real life challenges of implementation, including policy making, prevention in public places, dealing with social disorder and planning for the future.
Includes bibliographical references and index.
Keywords: Crime prevention